Social media, peer norms, and betel nut susceptibility and use: Evidence from early adolescents in Guam - Dalisay, Francis; Kawabata, Yoshito; Buente, Wayne; Pokhrel, Pallav; Benitez, Chantay; Herzog, Thaddeus (Frontiers in Communication, 2022)
Betel (areca) nut is an addictive psychoactive substance considered to be carcinogenic. Yet not much is known about factors that may be promoting betel nut use. To fill this void, the present study examines the roles of exposure to betel nut-related posts on social media and peer norms regarding betel nut use in explaining betel nut susceptibility and use among adolescents. We conducted a representative survey of early adolescents (N = 673) attending all public middle schools on Guam, a United States-Affiliated Pacific Island in the Western Pacific. Results showed that exposure to betel nut-related posts on social media was positively associated with peer descriptive norms regarding betel nut use. Specifically, the more frequent early adolescents were exposed to betel nut posts on social media, the more likely they were to perceive betel nut use to be more prevalent among their general peers and close friends. Additionally, early adolescents’ exposure to betel nut-related posts on social media was positively associated with both their susceptibility to use betel nut and reported use. Descriptive norms regarding close friends’ betel nut use was also positively associated with both susceptibility to and use of betel nut. However, descriptive norms regarding general peers’ betel nut use was unrelated with either betel nut susceptibility or use. Descriptive norms regarding close friends’ betel nut use mediated the relationships that exposure to betel nut posts on social media had with both betel nut susceptibility and betel nut use. Implications are discussed.